Shariah Information Disclosure and its Effect on Financial Perfomance among SMEs in Malaysia - Azman, Ain Noor; Ali, Noor Azman; Mahat, Fauziah; Daud, Zaidi Mat (Advances in Social Sciences Research Journal, 2020)
Introduction: Shariah disclosure has become an important aspect in a Small-Medium Enterprises (SMEs). The disclosure of shariah information would enhance the transparency and accountability of SMEs towards its stakeholders which in return helps promote the long-term profitability and sustainability. Objective: (1) examine the extensiveness of Shariah disclosure and (2) investigate the relationship between Shariah disclosure on product and services, financing, earnings and expenditure, social functions and environment and its effect on financial performance of SMEs in Malaysia. Methods: In total, 131 respondents comprised of owners and top management of SMEs in the state of Selangor, Kedah, Pahang, and Johor. The questionnaire was developed based on Shariah Index for Islamic Social Reporting and the data was analysed using multiple regression. Results: The findings indicated that Shariah disclosure on financing found to have significant relationship on the financial performance of SMEs. In contrast, products and services, earning and expenditure, social functions and environment were found to have no significant relationship on the financial performance of SMEs. The results also show that working environment for workers was disclosed extensively by SMEs while, earning expenditure on non-Shariah compliant the disclosure was less extensive.